Semi-Manual Processing Of Blood Clamps Waste into Chitosan Powder - Chiesa Salsabila; Candra Wahyuningsih; Diana Ayu Fitriana; Rina Sari Asih; Khoirin Nida; Rejeki Siti Ferniah (Research Collaboration Community (RCC), 2022)
Blood clams (Anadara granosa) are endemic clams found in Southeast Asia and East Asia. Blood clams are widely consumed by the public as seafood dishes in coastal food stalls. The great potential of blood clams will increase the waste of clam shells produced. The accumulation of shellfish waste will cause pollution and reduce environmental aesthetics. The chitin content in blood clam shells can be used as chitosan. Chitosan is a polymer of -(1-4) glucosamine which is formed when the acetyl group in chitin is substituted by hydrogen to become an amine group. Chitosan has antibacterial and antifungal properties. Isolation of chitosan was carried out through the stages of demineralization, deproteination, and deacetylation. The limited use of laboratories during the pandemic is a major obstacle in the isolation process of chitosan. This study aims to process blood clam shell waste into chitosan in a simple way on a home scale. Processing includes deproteination, demineralization, and deacetylation were done using tools and materials available at home. Laboratory equipment such as beakers could be replaced with pots, the reflux process was replaced by using a cloth to filter, and measuring cups were replaced with glasses. The research used 1500 grams of blood clam shell powder and produced 1050 grams of white chitosan with a slightly hard texture